2019
DOI: 10.1155/2019/3923574
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Life-Space Mobility and Cognitive Function in Older Adults: A Systematic Review

Abstract: Purpose. The purpose of this review is to investigate the relationship between life-space mobility and cognition in older adults. Methods. MEDLINE, Embase, CINAHL, and PsycINFO were searched through December 2018 for studies containing measures of life-space mobility and cognitive function. Two independent reviewers screened studies. Eligible studies were combined using a random-effects model, and heterogeneity was assessed using the I2. Results. Thirty-five articles were identified for review. A moderate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 72 publications
(233 reference statements)
4
50
1
4
Order By: Relevance
“…Younger age, having good compared to poor general medical health, less severe dementia, better physical performance, less apathy, more agitation, and living in a smaller unit were associated with on average wider LS throughout the study period. Associations with age, comorbidity, and dementia severity are supported by previous studies’ findings of community-dwelling older adults [ 7 , 12 , 14 ]. However, these characteristics are generally not modifiable or reversible.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Younger age, having good compared to poor general medical health, less severe dementia, better physical performance, less apathy, more agitation, and living in a smaller unit were associated with on average wider LS throughout the study period. Associations with age, comorbidity, and dementia severity are supported by previous studies’ findings of community-dwelling older adults [ 7 , 12 , 14 ]. However, these characteristics are generally not modifiable or reversible.…”
Section: Discussionsupporting
confidence: 78%
“…Group 4 residents were younger, had better physical performance and less severe dementia at admission compared to Group 2 residents. These three characteristics are associated with wider LS levels across populations [ 12 , 13 , 26 , 28 , 29 ]. These residents might have responded well to transitioning to NH care and benefited from the aid, services, and activities provided, facilitating them to increase and maintain their wide LS over time.…”
Section: Discussionmentioning
confidence: 99%
“…Modifiable factors were selected using Webber's conceptual framework of life-space mobility [9] and previous research evidence where factors that demonstrated an association with mobility were identified. Factors were categorized in accordance with Webber's framework, including physical [17,18,23], psychosocial [24,25] and cognitive determinants [26], alongside other factors that were highlighted in previous studies, such as pain [27], fatigue [28], driving status [29], nutrition [30,31], body mass index [32], smoking status [33,34] and vision [35].…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…However, in general, studies do agree that decreased cognitive skills impede moving in larger outdoor spaces. In addition, studies like De Silva et al (2019) [90] also describe an opposite effect stating that a reduced, homogenous life-space without special cognitive, auditory, or visual stimuli causes a decline in cognitive abilities with one LSA score of 41 points seemingly being the cut-off value leading to a steeper decline of cognition.…”
Section: Skillsmentioning
confidence: 99%